To Assessment of the Effectiveness of a Structured Educational Program on Women's Knowledge of Sexually Transmitted Diseases in Rural Areas of Ludhiana, Punjab: A Quasi-experimental Study - Sumandeep Kaur (International Journal of Evidence Based Nursing And Practices, 2023)
Background: Maintaining good health is of immeasurable value, as it empowers individuals to lead socially and economically fruitful lives. However, various disorders have the potential to disrupt one's health. Among these, sexually transmitted diseases (STDs) are the most prevalent disorders affecting the reproductive system and other bodily systems, resulting in significant consequences for both families and society. Sexually transmitted diseases (STDs) can be triggered by various microorganisms, including bacteria (like gonorrhea, syphilis, and Chlamydia), parasites (such as trichomoniasis), and viruses (for example, human papillomavirus, genital herpes, and HIV). While sexual activity plays a major role in the transmission of many infectious agents, it is important to note that infections can occur without sexual contact as well. Sexually transmitted diseases (STDs) exhibit various symptoms such as vaginal discharge (thick or thin, with colors like milky white, yellow, or green), itching in the vaginal area, blisters in the genital area (covered by underwear), rash in the genital area or vagina, burning and pain during urination, and painful intercourse. Screening serves as another diagnostic method for detecting STIs. One recommended screening test for individuals aged 13 to 64 years is a blood or saliva test that checks for the presence of human immunodeficiency virus (HIV), the virus responsible for causing AIDS. Furthermore, the Pap test is employed for the detection of cervical irregularities, which may encompass inflammation, precancerous alterations, and cancer, frequently linked to certain strains of the human papillomavirus (HPV). Our choice to conduct this study is based on the aim of evaluating and contrasting women's knowledge about sexually transmitted diseases in both the control and experimental groups. Materials and Methods: The researcher employed a convenient sampling approach to choose 60 participants, all of whom were women aged between 21 and 45 years. This group was further divided into a 30-member experimental group and a 30-member control group. The study was conducted in specific rural locations, namely, the village of Bassian in Ludhiana, Punjab. This village had a total population of 8165 and was located at a distance of 6 km from GHG College of Nursing in Raikot. From Akalgarh, a village situated in Ludhiana, Punjab, with a total population of 2000, the study indicated that the experimental group achieved the highest post-test mean knowledge score of 20.3, while the control group had a post-test mean knowledge score of 19.8. Therefore, the study's findings indicated that the experimental group had a higher average knowledge score after the test, compared to the control group. Conclusion: The study's results led to the formulation of several conclusions. Initially, the control group exhibited a pretest mean knowledge score of 15.7, while the experimental group had a slightly lower score of 14.46. After the assessment, it was observed that the control group had an average post-test knowledge score of 19.8, while the experimental group achieved a slightly higher score of 20.03. Importantly, it was found that the post-test knowledge score of women in the experimental group, concerning sexually transmitted diseases, was significantly higher than that of the control group, with a statistical significance level of p<0.05. No statistically significant correlations were detected between women's knowledge and the demographic factors that were considered.
Keywords: Knowledge; demographic factors; rural; sexually transmitted diseases; women